Antidiabetic Effectiveness of Ethanol Extract from Sweet Mango Leaves (Mangifera indica L. var. Arum Manis) on Blood Glucose Levels in Streptozotocin-Induced Male Mice (Mus musculus L.) - Marisha, Rara Widiya; Astriani Natalia Br Ginting; Daimah Wirdatus Sanaun Harahap (Jurnal Kesehatan dan Kedokteran, 2026)
Diabetes mellitus (DM) is a growing public health concern worldwide, particularly in Indonesia, where its prevalence continues to rise, causing significant health and economic burdens. The need for effective, accessible, and safe therapies is critical, as current treatments often come with side effects and limitations. Alternative natural treatments, such as herbal remedies, are being explored for their potential to offer safer and more sustainable options for managing DM. Objective: This study aims to evaluate the antidiabetic effectiveness of ethanol extract of sweet mango leaves (Mangifera indica L. var. sweet mango) on reducing blood glucose levels in streptozotocin (STZ)-induced diabetic mice. Methodology: A true experimental post-test only control group design was employed using mice (Mus musculus) divided into six groups: normal control, negative control (STZ), positive control (glibenclamide), and three treatment groups of mango leaf extract with doses of 50, 100, and 150 mg/kgBW. The extraction was carried out using the maceration method with 70% ethanol, and the antidiabetic activity was tested over a 15-day period. Results: The results showed that administration of ethanol extract of sweet mango leaves significantly reduced blood glucose levels (p < 0.001) compared to the negative control. A dose-response pattern was observed, with a dose of 150 mg/kgBW providing the most significant blood glucose lowering effect, closely approaching the effectiveness of glibenclamide. Discussion: The antidiabetic activity of the extract is thought to be related to its bioactive compounds, such as flavonoids, phenolics, and mangiferin, which are believed to enhance insulin sensitivity, inhibit gluconeogenesis, and protect pancreatic β cells from oxidative stress. Originality and Contribution: This study provides new insights into the antidiabetic potential of the ethanol extract of sweet mango leaves (Mangifera indica var. Arum Manis), a variety not extensively studied for its effects on diabetes. The research contributes to the growing body of knowledge on natural-based therapies for DM, offering an alternative to conventional treatments with potentially fewer side effects and wider accessibility. The findings support the further development of mango leaf extract as a natural candidate for diabetes management.